2015
DOI: 10.1007/s11606-015-3247-0
|View full text |Cite
|
Sign up to set email alerts
|

Community Health Worker Interventions to Improve Glycemic Control in People with Diabetes: A Systematic Review and Meta-Analysis

Abstract: OBJECTIVES:We set out to review the efficacy of Community Health Worker (CHW) interventions to improve glycemia in people with diabetes. METHODS: Data sources included the Cochrane Central Register of Controlled Trials, Medline, clinicaltrials.gov, Google Scholar, and reference lists of previous publications. We reviewed randomized controlled trials (RCTs) that assessed the efficacy of CHW interventions, as compared to usual care, to lower hemoglobin A1c (A1c). Two investigators independently reviewed the RCTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(115 citation statements)
references
References 36 publications
4
110
0
1
Order By: Relevance
“…Two recent reviews of CHW interventions found that some, but not all, randomized trials show benefit for HbA1c [29,30]. Our results may be due to the fact that stress management, rather than diabetes self-care per se, was the focus of the intervention.…”
Section: Discussionmentioning
confidence: 74%
“…Two recent reviews of CHW interventions found that some, but not all, randomized trials show benefit for HbA1c [29,30]. Our results may be due to the fact that stress management, rather than diabetes self-care per se, was the focus of the intervention.…”
Section: Discussionmentioning
confidence: 74%
“…5355 CHW programs have existed for more than a century in developing countries for infectious disease management 56 and maternal child health. 5759 Among the adult chronic diseases, CHWs have been shown to improve health outcomes for asthma, hypertension, heart disease, diabetes, and HIV, as well as improve disease self-management, disease prevention, pregnancy outcomes, and healthcare utilization.…”
Section: Community Health Workersmentioning
confidence: 99%
“…[1][2][3] As value-based payment models expand, providers will have more flexibility to fund CHWs with global budgets, or payers may elect to reimburse for CHW services. [4][5][6] The emerging evidence base on CHW programs 7 for the prevention and management of chronic diseases includes systematic reviews concluding that CHW interventions can improve overall health outcomes 8 and outcomes for patients with heart disease, stroke, 9 type II diabetes, [10][11][12] HIV, 13 and asthma 2,14 and for vulnerable patients with or at risk for a variety of chronic diseases or cancer. 15 Other systematic reviews have also documented the costs and cost-effectiveness of CHW programs, 15 but none, outside of low and middle-income countries, 16 have examined the impact of CHWs on the utilization of health services by patients with chronic conditions.…”
Section: Introductionmentioning
confidence: 99%